Menilai Pengaruh Store Atmosphere dan Kualitas Produk terhadap Minat Beli Pelanggan di Fore Café Palembang Trade Center Mall - Hanna Vinesia Silabam; Vito Yudistio; Jessie Victoria Della Puspita (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
This study aims to analyze the effect of store atmosphere and product quality on customer purchase intention at Fore Cafe Palembang Trade Center. The research uses a quantitative approach with descriptive-explanatory method, collecting data through questionnaires from 153 respondents who have visited the cafe. The results of the analysis show that store atmosphere and product quality have a positive and significant influence on customer purchase intention. Store atmosphere components, such as interior design, lighting, music, and cleanliness, are proven to play a role in creating a pleasant customer experience. On the other hand, product quality, including taste, menu variety, and attractive presentation, is a major factor in driving purchase intention. These findings confirm the importance of optimizing store atmosphere and product quality as effective business strategies to increase the attractiveness and sustainability of café businesses amidst competition.